english Penerapan Model Pembelajaran ASICC (Adapting, Searching, Interprenting, Creating, and Communicating) untuk Meningkatkan Kreativitas Fisika Siswa SMAN 1 Perhentian Raja - Ranti Amelia Sari; Zulirfan Zulirfan; M. Rahmad (Postgraduate, University of Mataram, 2023)
This research aims to improve students' physics creativity skills through the application of the ASICC learning model. This research is considered necessary because the results of the initial ability analysis of students through teacher and student respondents gave low results of 55 with less categories. This study is a class action research conducted as many as two cycles. Matter in the first cycle is sound waves and matter in the second cycle is light waves. This research was conducted at SMAN 1 Perhentian Raja Kampar regency, Riau province, with the research subjects of grade XI science students as many as 25 people, 10 men and 15 women. This step in research starts from the precycle stage (initial capability analysis), making learning tools and instruments, validating devices and instruments, actions, evaluation, and reflection. Assessment of student creativity is carried out every time the meeting is assessed by the teacher himself through the instrument of student creativity. The student work created is a simple work that can be completed in one meeting. The students' work is in the form of concept maps, poster designs, and data graphics. The average results of students' creativity skills obtained for cycle 1 to cycle 2 are, for cycle 1 with an average of 70.85 and cycle 2 with an average of 77.5. This increase can be seen from the change in the value of creativity for the same work in different cycles